Investigation Into Surface Treatment On Fatigue Life For Cylinder Block Of Linear Engine Using Frequency Response Approach. - M. M., Rahman; R. A., Bakar; M. S. M., Sani; M. M., Noor (2008)
Aluminum alloys are one of the most promising materials selections for automobiles parts and electrical components to reduce their weight and to increase their specific strength. This paper presents the effect of surface treatment on the fatigue life of the vibrating cylinder block for a new two-stroke free piston engine using random loading conditions. The finite element modeling and analysis were performed using a computer aided design and finite element analysis codes respectively. In addition, the fatigue life prediction was carried out using finite element based fatigue analysis code. The material aluminum alloys are considered in this study. The frequency response approach was applied to predict the fatigue life of cylinder block using different load histories. Based on the finite element results, it is observed that there is a significant variation between the nitriding treatment and untreated cylinder block of free piston engine. The obtained results indicate that the nitrided treatment produces longest life for all loading conditions. Therefore, the nitriding process is one of the promising surface treatments for aluminum alloy parts to increase the fatigue life of the linear engine cylinder block.